REKONSTRUKSI SEJARAH DAN DINAMIKA PERKEMBANGAN KAJIAN AL-QUR'AN DI EROPA : Sejarah dan Perkembangan Masuknya Al-Qur'an di Eropa serta Perkembanganya - Al Fiqri, Haikal (FIHROS: Jurnal Sejarah dan Budaya, 2024)
The Qur'an is not only studied and studied by Muslims but also by non-Muslims. The entry of the Qur'an into the territories of European and Western nations is a manifestation and clear evidence of this statement. Of course, people who study the Qur'an come from groups outside Islam, in fact history records that the Qur'an was first translated into Latin by a priest named Petrus Venerabilis. One of the reasons is the increase in European people, especially outside Spain, in cultural contact with Islam so that they try to study and study Islam more deeply, including the Qur'an and the history of the Prophet Muhammad as the recipient of revelation. The arrival of the Al-Qur'an in Europe occurred during the golden age of Islam, namely the practice of hellenation carried out by Arabic-Islam against the Greco-Roman tradition which became the center of world civilization at that time. In the end, many nations, including Western Europe, conducted studies on Islam. At the same time, this era was the dark ages, for Europeans this was especially seen in science and philosophy which experienced decline due to church doctrine. However, the thing that has become the center of attention is the Venerable Pastor's words that Christians must attack Islam through words, no longer through war. Of course, this is a very controversial matter because in this case it seems as if the Qur'an is being used as an object that can be played with by them. Furthermore, the Qur'an in Europe itself has progressed to date. This is proven by the study of the Koran which was carried out by Muslim academics who studied there. Of course, this step must be a step and effort to spread Islam in European countries where Muslims themselves are a minority in that country. However, of course this method does not mean it will not have a negative impact on the authenticity of Islam itself. Of course there will be those who doubt the revelation of the Qur'an and this has been proven to exist